Financial Feasibility Of Business On Fast Fashion Startup: A Case Study Of Udo Innovate’s Offline Store Establishment Project - Purba, Rafael Abrahim Immanuel; Irawan, Atika (Journal Integration of Social Studies and Business Development, 2024)
Fast fashion, noted for its trendy and affordable clothing, has gained significant traction in Indonesia, with the market expected to reach $22.66 billion by 2024 and a compound annual growth rate (CAGR) of 3.31% (Statista). UDo Innovate, a fast fashion company collaborating with the skateboarding community in Bandung, faces challenges in optimizing its marketing strategies due to low sales from online-only efforts. The company seeks to enhance its market presence through an omnichannel strategy, incorporating offline platforms. However, the financial feasibility of this shift has not been previously assessed. This study aims to evaluate the financial viability of establishing a retail store as part of UDo Innovate's omnichannel approach. Financial feasibility is analyzed using the payback period, net present value (NPV), and internal rate of return (IRR), with risk assessed through scenario analysis. The results reveal that setting up an offline store is financially viable within two years, with a payback period of 1.66 years, an NPV of Rp583,921,410, and an IRR of 49.53%. The analysis also considers funding options, recommending a loan from Bank Mandiri with a 6% annual interest rate and an 11% tax rate. This results in a weighted average cost of capital (WACC) of 5.63%, which is lower than the cost of utilizing the owner's capital at 6.38%. The study concludes that the investment in an offline retail store is financially sound and aligns with UDo Innovate's strategic goals.